Africa wired - Jocelyne Sambira (Africa Renewal, 2013)
Five flashlight bulbs, an old car battery and a solar panel were the only tools 11-year-old Richard Turere used to put together a system of lights that keeps his family’s cattle safe from lions. His simple invention costs less than 10 and it’s easy to install and maintain. It also works to prevent elephants from trampling people’s crops.